1992
DOI: 10.1007/bf01358265
|View full text |Cite
|
Sign up to set email alerts
|

A critical discussion of Kellman and Shipley's (1991) theory of occlusion phenomena

Abstract: Kellman and Shipley (1991) recently advanced a new theory to explain the perception of partly occluded objects and illusory figures. The theory is a formalization of the Gestalt law of good continuation. In this paper we describe their account of occlusion when the contour of the occluder is completely specified by a display. Next, we outline some critical objections and present a number of counterexamples. Finally, we compare their theory with Wouterlood and Boselie's (in this issue) model of occlusion phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
3
17
1
Order By: Relevance
“…The given local completion in figure 2b is based on linear good continuation and agrees, for example, with the model proposed by Wouterlood and Boselie (1992). [Note that the approach of Kellman and Shipley (1991) would not predict completion here because the edges do not meet the relatability criterion; see also Boselie and Wouterlood (1992). ]…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The given local completion in figure 2b is based on linear good continuation and agrees, for example, with the model proposed by Wouterlood and Boselie (1992). [Note that the approach of Kellman and Shipley (1991) would not predict completion here because the edges do not meet the relatability criterion; see also Boselie and Wouterlood (1992). ]…”
supporting
confidence: 72%
“…This principle was referred to as the reliability criterion. Boselie and Wouterlood (1992) criticised this principle on several grounds and proposed their own local model (Wouterlood and Boselie 1992). In their good-continuation model, it is assumed that there is a tendency to describe a pattern by the smallest number of contour elements and changes of direction within and between these contour elements.…”
Section: Introductionmentioning
confidence: 99%
“…We agree with Kellman and Shipley (1991) that splitting is (mainly) due to local factors, although for a critique of the claim that completions do not occur for angles less than 908 one must see Boselie and Wouterlood (1992). However, we disagree with Figure 2.…”
mentioning
confidence: 46%
“…According to this theory, completion tends to produce the impression of the most regular shapes (Buffart and Leeuwenberg, 1981). However, other researchers have shown that observers do not always perceive the most regular shapes (Boselie and Wouterlood, 1992). Other theories ascribe amodal completion to the use of volume cues to form the image (Tse, 1999) or common depth planes (Nakayama and Shimojo, 1992).…”
Section: Instant Perceptual Filling-in Dependent On Stimulus Configurmentioning
confidence: 99%